Управління витратами компанії Inditex - Даценко, Марія Олександрівна (My University, 2024)
Inditex, a global leader in the fashion retail sector, has garnered significant attention with its creative business strategy and outstanding financial results. This bachelor’s project aims to offer valuable insights into the operational efficiency and financial stability of Inditex, S.A., by examining the nuances of the company’s profitability dynamics. Important information about Inditex’s financial performance and strategic positioning in the global retail industry can be obtained from a comparative study of the company’s profitability trends from the fiscal years 2020 to 2023. A crucial aspect of financial management is profitability analysis, which sheds light on the efficiency, performance, and strategic positioning of a company. This bachelor’s thesis explores the significance, techniques, and theoretical foundations of profitability analysis with a specific focus on the case of Inditex, S.A., a major player in the global fashion and retail industry. The theoretical part of the review provides a thorough understanding of profitability indicators and cost analysis. Cost analysis examines all company expenses, such as operating expenses, cost of goods sold, net sales, marginal costs, and absorption costs. Key indicators like gross profit margin, net profit margin, return on equity (ROE), contribution margin, return on assets (ROA), and return on investment (ROI) are also presented in the profitability analysis. The importance of profitability analysis in strategic decision-making, performance evaluation, and investor confidence in the business environment is highlighted in this section. This thesis aims to clarify the dynamics of Inditex’s profitability through an in-depth examination of its financial performance. The study looks at key financial indicators and measures to provide insights into the company’s competitive advantage, operational efficiency, and potential for creating long-term value. The methodology used to analyze Inditex’s profitability is described in the methodological section. It explains the procedures and tools used to gather data, including annual reports and financial statements. Additionally, it provides a rationale for the chosen methodology and clarifies its significance for the analysis, ensuring thorough and meaningful research. An extensive overview of Inditex’s financial performance is provided in the results section, which begins with a company profile and a list of selected accounting policies. An in-depth analysis of income statements, balance sheets, and key financial indicators is included, offering insights into intangible assets, equity, net sales, gross profit, operating expenses, and net profit. Based on parameters such as gross profit margin, net profit margin, gross operating profit (EBITDA) and EBITDA margin, net operating profit (EBIT) and EBIT margin, contribution margin, ROA, ROE, and ROI, the profitability analysis assesses Inditex’s performance and provides meaningful information about the company’s financial condition and profitability. The paper provides thorough summaries of the company’s financial performance and strategic approach across several sections. The company profile, which describes its chosen accounting policies, comes first. Next, we examine the balance sheet, which includes information on equity, long-term liabilities, short-term liabilities, total assets, and intangible assets. Important financial indicators are highlighted to understand the company’s financial stability. In the income statement section, net sales, cost of goods sold, gross profit, operating expenses, profit, amortization, depreciation, financial results, profit before tax, income tax, and net profit are covered in detail. This detailed breakdown allows for a comprehensive understanding of the company’s revenue sources, costs, and profitability drivers. Overall, this bachelor’s thesis contributes to the understanding of profitability analysis within the fashion and retail industry by providing detailed information on Inditex’s strategic focus and financial management methods. The aim is to provide stakeholders with valuable information for informed decision-making and strategic planning through a thorough analysis of financial data and performance indicators
Cost management of the company "Inditex, S.A."
Keywords: управління; витрати; управління витратами; компанія; management; costs; cost management; company; kosten; kostenmanagement; unternehmen